179k views
1 vote
If g(x)=x/1+2x, how do you find g'(a) and use it to find an equation of the tangent line to the curve at the point (1, 1/3).

User Matanox
by
5.6k points

1 Answer

4 votes

Answer:


g'(a)=(1)/(\left(2 a + 1\right)^(2))

equation of tangent at (1,1/3) is:


y = (1)/(9)x+(2)/(9)\\

Explanation:


g(x) = (x)/(1+2x)


g'(x) = (d)/(dx)\left((x)/(1+2x)\right)

this differentiation can be easily done using the quotient rule:


d\left((u)/(v)\right) = (vu'-uv')/(v^2)

here,

u = x, and v = 1+2x.

u' = 1, and v' = 2

The derivative of u and v are written as u' and v'.


g'(x)=((1+2x)(1)-(x)(2))/((1+2x)^2)\\g'(x)=(1)/(\left(2 x + 1\right)^(2))

this is the derivative of g(x) and it is denoted by g'(x)

g'(a) means to simply replace all the x's with a in the above equation


g'(a)=(1)/(\left(2 a + 1\right)^(2))

to find the equation of the tangent to this curve at (1,1/3)

we need to know the slope of the tangent at that very point. This can be found using g'(x). since g'(x) only takes x as the input. we'll only use the x-coordinate of the point (1,1/3)


g'(1)=(1)/((2(1) + 1)^(2))


g'(1)=(1)/(9)

the slope of the tangent to the curve at the point (1,1/3) is 1/9

to find the equation of the line we'll use:


(y-y_1) = m(x-x_1)\\

here m is the slope, and (x1,y1) = (1,1/3)


(y-(1)/(3)) = (1)/(9)(x-1)\\

simplify:


y = (1)/(9)x-\dfra{1}{9}+(1)/(3)\\


y = (1)/(9)x+(2)/(9)\\

this is the equation of the tangent to the curve g(x) at the point (1,1/3)

User John Kattenhorn
by
6.2k points